The people behind the papers (Development, 2019)
Skip to Next Section - Radial growth in plants is driven by proliferating cells in the cambium that give rise to the vascular tissues of xylem and phloem, and increases plant girth. However, the identity and dynamics of the stem cells that drive this crucial process remain poorly understood. A paper in this issue of Development now characterises cambial stem cell activities in the hypocotyl of Arabidopsis. We caught up with first author Dongbo Shi and his supervisor Thomas Greb, Heisenberg Professor at the Centre for Organismal Studies in Heidelberg University, Germany, to find out more about the story.